Maskulinitas pada Budaya Kejahatan Geng Klitih: Sebuah Analisis Konstruksi Sosial - Harahap, Chisa Belinda; Triyoga, Anwar Ibrahim; Prafitri, Wilma (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
This study aims to examine the social construction of masculinity in the phenomenon of klitih gang crime in Yogyakarta. Klitih crimes, involving male adolescents, are viewed as a form of criminal subculture oriented towards violence as a means of gaining recognition and social existence. This research employs a qualitative method with a case study approach. Data were obtained through document analysis, media reports, and online platforms used by klitih gang members. This descriptive qualitative approach provides in-depth insights into the motivations and perceptions of klitih perpetrators in constructing their masculine identity through violence. The findings reveal that hegemonic masculinity plays a significant role in the violent actions committed by the klitih gang. Klitih gang members tend to use violence not for economics gain but as a tool to enhance their social status and reinforce an aggressive and dominant masculine identity. This phenomenon reflects how societal norms surrounding masculinity can drive violent behavior among adolescents. This study is expected to contribute to cultural criminology studies and help in formulating social intervention strategies to address youth violence in Yogyakarta.Keywords: Cultural criminology, hegemonic masculinity, klitih gang, social construction,youth violence